Europeanization and Nation-Building Process: The Case of Scottish Cultural Heritage Policies - Cantin, Caroline (Université d'Ottawa / University of Ottawa, 2014)
Our thesis discusses the issue of Europeanization in light of Scottish cultural heritage policies since devolution. This sectoral public policy is not the subject of much attention, but this thesis wants to fill the gap. This thesis also raises the questions of identity in the field of cultural heritage. We tend to determine the forces that are involved in the construction of the Scottish identity post-devolution. This work is done by keeping in mind the fact that Scotland is torn between the European and the British influences. In order to operationalize our object of study, we identify six variables that are part of the EU public policies. These variables are the economic and social justifications of cultural public policies, the importance of cultural democracy, the cultural development of regions, the EU policy process and the decision-making process, the emphasis placed on the development of partnerships and the ambivalence of the notion of the EU identity. Our analysis reveals that all of these variables are present in Scottish cultural heritage policies. The omnipresence of all these variables is significant. Nevertheless, because of the limited extent of our work, we consider that it is more appropriate to assert that policy convergence is taking place in Scotland instead of concluding that Scottish cultural heritage policies are openly Europeanized. Our thesis also shows that the presence of these variables in Scottish cultural heritage policies since devolution is an efficient way for Scotland to assert its difference from the UK. Indeed, for almost all of these variables, Scotland’s position tends to differ from the UK.
Keywords: Europeanization; Scotland; Cultural Heritage Policies; Identity